Rainfall shocks and risk aversion: Evidence from Southeast Asia - Sabine Liebenehm; Nele Degener; Eric Strobl (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2018)
Empirical studies advocating the temporal variability of risk attitudes suggest that adverse covariate shocks significantly alter risk attitudes over time, but there is no consensus on the direction. In this paper, we investigate whether risk aversion increases or decreases in response to shocks. To do so, we combine individual-level panel data with historical rainfall data for rural Thailand and Vietnam. Our econometric analysis shows that temporal variability in risk attitudes is driven by rainfall shocks. Both severe shortages and excesses appear to increase individuals' risk aversion. Contrary to expectations, we find that this impact is lower for farmers than for non-farmers. We can explain this result by the heterogeneous composition of non-farmers and by farmers' ability to mitigate rainfall shocks. Our findings have potentially important implications especially for developing countries in that adverse shocks can increase poor people's risk aversion and may lead to decisions that perpetuate their lives in poverty.
Keywords: C23; D9; Q54; 330; Rainfall; Risk attitudes; Risk mitigation